2022
DOI: 10.1126/sciadv.abo7566
|View full text |Cite
|
Sign up to set email alerts
|

The impact of C-tactile low-threshold mechanoreceptors on affective touch and social interactions in mice

Abstract: Affective touch is necessary for proper neurodevelopment and sociability. However, it remains unclear how the neurons innervating the skin detect affective and social behaviors. The C low-threshold mechanoreceptors (C-LTMRs), a specific population of somatosensory neurons in mice, appear particularly well suited, physiologically and anatomically, to perceive affective and social touch. However, their contribution to sociability has not been resolved yet. Our observations revealed that C-LTMR functional deficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Our data strongly implicate an additional type of touch neuron, the perineal cLTMRs, as crucial drivers of sexual function. Previous studies in mice and humans suggest specialized roles for cLTMRs in conveying affective and pleasurable touch ( 40 , 41 ). Thus, it is of note that five individuals without PIEZO2 function described sexual activity as satisfying and rewarding despite marked mechanosensory deficits and clinical evaluations of hypo-orgasmia (men) and anorgasmia (women).…”
Section: Discussionmentioning
confidence: 96%
“…Our data strongly implicate an additional type of touch neuron, the perineal cLTMRs, as crucial drivers of sexual function. Previous studies in mice and humans suggest specialized roles for cLTMRs in conveying affective and pleasurable touch ( 40 , 41 ). Thus, it is of note that five individuals without PIEZO2 function described sexual activity as satisfying and rewarding despite marked mechanosensory deficits and clinical evaluations of hypo-orgasmia (men) and anorgasmia (women).…”
Section: Discussionmentioning
confidence: 96%
“…It has previously been shown that just three types of LTMR present within the skin respond directly to deflection of the hair fiber: Aδ-RA-LTMRs, Aβ-RA-LTMRs, and C-LTMRs ( 4 ). While Aβ-LTMRs and Aδ-LTMRs respond to a single deflection of the hair fiber caused by a stroke or breeze, C-LTMRs are only activated by light and slow touch and have a negligible role in processing spatial and qualitative information ( 5 , 6 ). Aβ-Field-LTMRs and Aβ-SA-LTMR both innervate hair follicles but unexpectedly do not respond to hair fiber deflection.…”
Section: Discussionmentioning
confidence: 99%
“…In glabrous skin (nonhairy skin located on the palms of our hands and soles of our feet), this transfer facilitates an understanding of our external surroundings ( 3 , 4 ). Hairy skin also contains C-LTMRs, a specific type of tactile neuron that is not present on glabrous sites and is involved in processing affective touch response ( 5 , 6 ). Various mechanical stimuli, such as stretch, skin movement, compression, or hair fiber deflection can activate these different classes of mechanoreceptors within the skin ( 4 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could reflect a differential role for TRPV4 in mediating responses to mechanical stimuli that are of distinct valences and detected by separate fiber types. A-fibers (eg, low-threshold mechanoreceptor [LTMR] Ab) and C LTMRs likely mediate dynamic light touch with a brush 44,52,57,73,79 whereas punctate or pressure stimuli are associated several types of sensory fibers and transduction mechanisms, including A-fibers and Cfibers, under inflammatory conditions. 55,58 Indeed, most DRG neurons that express TRPV4 are small diameter nociceptors, 103,104 which tend to give rise to unmyelinated C-fibers or lightly myelinated Ad-fibers.…”
Section: Trpv4 Block Attenuates Mechanical Hypersensitivity To Puncta...mentioning
confidence: 99%